In Vivo Tracking of Systemically Administered Allogeneic Bone Marrow Mesenchymal Stem Cells in Normal Rats through Bioluminescence Imaging. (17th August 2016) - Cao, Juan; Hou, Shike; Ding, Hui; Liu, Ziquan; Song, Meijuan; Qin, Xiaojing; Wang, Xue; Yu, Mengyang; Sun, Zhiguang; Liu, Jinyang; Sun, Shuli; Xiao, Peixin; et al.
Abstract : Recently, mesenchymal stem cells (MSCs) are increasingly used as a panacea for multiple types of disease short of effective treatment. Dozens of clinical trials published demonstrated strikingly positive therapeutic effects of MSCs. However, as a specific agent, little research has focused on the dynamic distribution of MSCs after in vivo administration. In this study, we track systemically transplanted allogeneic bone marrow mesenchymal stem cells (BMSCs) in normal rats through bioluminescence imaging (BLI) in real time. Ex vivo organ imaging, immunohistochemistry (IHC), and RT-PCR were conducted to verify the histological distribution of BMSCs. Our results showed that BMSCs home to the dorsal skin apart from the lungs and kidneys after tail vein injection and could not be detected 14 days later. Allogeneic BMSCs mainly appeared not at the parenchymatous organs but at the subepidermal connective tissue and adipose tissue in healthy rats. There were no significant MSCs-related adverse effects except for transient decrease in neutrophils. These findings will provide experimental evidences for a better understanding of the biocharacteristics of BMSCs.